Dysregulated YAP1/TAZ and TGF-β signaling mediate hepatocarcinogenesis in Mob1a/1b-deficient mice - Nishio, Miki; Sugimachi, Keishi; Goto, Hiroki; Wang, Jia; Morikawa, Takumi; Miyachi, Yosuke; Takano, Yusuke; Hikasa, Hiroki; Itoh, Tohru; Suzuki, Satoshi O.; Kurihara, Hiroki; Aishima, Shinichi; et al. (Proceedings of the National Academy of Sciences - PNAS, 2016)
Mps One Binder Kinase Activator (MOB)1A/1B are core components of the Hippo pathway that coactivate large tumor suppressor homolog (LATS) kinases. Mob1a/1b double deficiency in mouse liver (LMob1DKO) results in hyperplasia of oval cells and immature cholangiocytes accompanied by inflammatory cell infiltration and fibrosis. More than half of mutant mice die within 3 wk of birth. All survivors eventually develop liver cancers, particularly combined hepatocellular and cholangiocarcinomas (cHC-CCs) and intrahepatic cholangiocellular carcinomas (ICCs), and die by age 60 wk. Because this phenotype is the most severe among mutant mice lacking a Hippo signaling component, MOB1A/1B constitute the critical hub of Hippo signaling in mammalian liver. LMob1DKO liver cells show hyperproliferation, increased cell saturation density, hepatocyte dedifferentiation, enhanced epithelial–mesenchymal transition and cell migration, and elevated transforming growth factor beta(TGF-β)2/3 production. These changes are strongly dependent on Yes-Associated Protein-1 (Yap1) and partially dependent on PDZ-binding motif (Taz) and Tgfbr2, but independent of connective tissue growth factor (Ctgf). In human liver cancers, YAP1 activation is frequent in cHC-CCs and ICCs and correlates with SMAD family member 2 activation. Drug screening revealed that antiparasitic macrocyclic lactones inhibit YAP1 activation in vitro and in vivo. Targeting YAP1/TAZ with these drugs in combination with inhibition of the TGF-β pathway may be effective treatment for cHC-CCs and ICCs.